Implementasi dan Analisis Simulasi QOS dan Perfomance Device dengan Menggunakan ONOS dan Iperf3 - I Putu Agus Eka Pratama; I Made Adhiarta Wikantyasa (Jurnal Informatika Universitas Pamulang, 2019)
Internet have evolved so rapidly in this day and age from where user only can access to internet service through cable UTP(LAN) and now user can access it from every where through nirkable (Wireless Network) and from this improvement it caused lots of device connected and heavy traffic coming in and out from a network. Because of this situation the network industry come with a new idea using a new network architecture that known as Software Defined Network (SDN). Software Defined Network (SDN) is a new way to manage, design and implementing network architecture where data flow from the control plane separated from the hardware. Network industry believe that SDN can change the network architecture that people using now that known as Traditonal Network because SDN can overcome the weakness of Tradional network that tend to be closed and distributed can be changed by SDN to be open source, can be programmed and can be controlled centrally. In this research will be implementing and analys simulation Quality Of Service (QOS) and Perfomance device openflow switch using ONOS as controller to monitor the device perfomance and iperf3 as a Quality Of Service testing.